(untitled) (Web of Teachers: Inderscience Research, 2025)
This article discusses the relevance and possibilities of using information and communication technologies (ICT) in music education, the ICT tools and methods applied in music lessons, stages of ICT integration, and the importance of digital skills for music teachers.